Malaysia halal trust : between reality and challenges - Soraji, Azis Jakfar; Awang, Mohd Daud; Mohd Yusoff, Ahmad Nasir (International Organization Center of Academic Research, 2017)
Public confidence regarding the permissibility of certain products or whether it is lawful, particularly for Muslims, founded through the display or the label to verify the halal certification issued by an authorized organization or recognized. Accordingly, the Department of Islamic Development Malaysia (JAKIM) is an organization that has the authority to issue halal certificates, especially in Malaysia. Islam has laid down rules and regulations for driving humanity to adhere to the principles of Islam prescribed in the Quran and Hadith. The research methodology of this paper is to use library research methods. This article describes the rules and regulations mentioned in the Quran and hadith which are the two primary sources of Islam. This article also describes recent developments in the halal industry conducted by the Malaysian government. In fact, it has been a goal of the government to make Malaysia a global halal hub. The purpose of this article is to introduce Malaysia as a halal hub at the international level and to share experience in the challenges and problems when conducting activities related to the halal industry. Finally, some proposals for improving the operations of halal in Malaysia has been proposed by some academics involved, so it provides an opportunity for a broad agenda for future research in the halal industry in Malaysia.